Pembentukan Gerakan Muslimah Wahdah Islamiyah 1985-1991: Perspektif Sosiologi Politik - Jurdi, Syarifuddin; Aksa, Aksa; Syarif, Ashila Salsabila (Jurnal Sosiologi USK (Media Pemikiran & Aplikasi), 2024)
The political policy of the Indonesian government between the 1970s and 1980s was oriented towards political stability by limiting ideological debate and the polarization of society. The policy of political party fusion succeeded in limiting the space for political debate, while the implementation of the single principle of Pancasila succeeded in producing internal polarization among Muslims. The policy encouraged the formation of movement organizations among Muslims, especially the embryonic Muslimah of Wahdah Islamiyah in 1985. This study uses a qualitative method using the perspective of social movements, finding several things: first, the formation of the Wahdah Islamiyah Muslimah movement as a response of salafi groups to the implementation of the single principle of Pancasila in 1985 and the policy of prohibiting the use of hijab for Muslim students issued by the Ministry of Education and Culture of the Republic of Indonesia. These two policies become the source of legitimacy for the formation of the movement organization; secondly, the Muslimah movement, in its social action, pays attention to advocacy and strengthening the role of women, especially advocacy for students who face psychological and physical pressure due to the hijab ban policy. Muslim women who remain consistent in wearing the hijab must choose between removing the hijab to remain in government schools or leaving to attend private schools. In addition to students, the Muslimah movement also mobilizes the power of female students to be active in religious social activities; third, the Wahdah Muslimah movement is an instrument of cadre recruitment and expansion of movement identity.AbstrakKebijakan politik pemerintah Indonesia antara dekade 1970-an dan 1980-an berorientasi pada stabilitas politik dengan membatasi perdebatan ideologis dan polarisasi masyarakat. kebijakan fusi partai politik berhasil membatasi ruang perdebatan politik, sementara pemberlakuan asas tunggal Pancasila berhasil memproduksi polarisasi internal umat Islam. Kebijakan tersebut mendorong terbentuknya organisasi pergerakan di kalangan Islam, khususnya terbentuknya embrio Muslimah Wahdah Islamiyah pada 1985. Studi ini menggunakan metode kualitatif dengan menggunakan perspektif gerakan sosial, menemukan beberapa hal; pertama, pembentukan gerakan muslimah Wahdah Islamiyah sebagai respons kelompok salafi terhadap pemberlakuan asas tunggal Pancasila pada 1985 dan kebijakan pelarangan menggunakan jilbab bagi pelajar muslimah yang dikeluarkan oleh Departemen Pendidikan dan Kebudayaan RI. Dua kebijakan ini menjadi sumber legitimasi pembentukan organisasi pergerakan; kedua, gerakan muslimah dalam aksi sosialnya memberikan perhatian pada advokasi dan penguatan peran perempuan, khususnya advokasi terhadap pelajar yang menghadapi tekanan psikologis dan fisik akibat kebijakan pelarangan jilbab, muslimah yang tetap konsisten menggunakan jilbab harus memilih antara melepaskan jilbab untuk tetap sekolah pada sekolah-sekolah pemerintah atau keluar untuk mengikuti sekolah swasta. Selain pelajar, gerakan muslimah juga menggalang kekuatan dari kalangan mahasiswi untuk aktif dalam kegiatan sosial keagamaan; ketiga, gerakan muslimah Wahdah adalah instrumen rekruitmen kader dan perluasan identitas gerakan.